A phosphate-based anticorrosive coating

By adding modified basalt fibers and other components to water-based anti-corrosion coatings, the shortcomings of existing coatings in terms of wear resistance, corrosion resistance and aging resistance are solved, and the corrosion resistance of the coatings is significantly improved.

CN119410180BActive Publication Date: 2025-03-18SICHUAN IND ENVIRONMENT MONITORING & RES INST
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510013738.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-01-06
Publication Date
2025-03-18
Estimated Expiration
2045-01-06

AI Technical Summary

Technical Problem

Existing water-based anti-corrosion coatings have poor wear resistance, corrosion resistance and aging resistance, and epoxy coatings are not resistant to light and salt spray resistance.

Method used

Using phosphate-based anticorrosion coatings, the coating's wear resistance, corrosion resistance and aging resistance are improved by adding modified basalt fibers, polyphosphate, inorganic curing agents and retarders.

Benefits of technology

It significantly improves the adhesion, corrosion resistance, wear resistance and aging resistance of the paint, and can more effectively prevent corrosion of metal equipment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The present invention discloses a phosphate-based anticorrosive coating, and relates to the technical field of anticorrosive coatings. The coating comprises: dihydrogen phosphate, polyphosphate, filler, inorganic curing agent, retarder, modified basalt fiber, and water; wherein the preparation method of the modified basalt fiber comprises the following steps: taking basalt fiber, adding acid to it for acid etching, separating, washing and drying it after the acid etching to obtain the acid-etched basalt fiber; taking the acid-etched basalt fiber, adding it to water and evenly dispersing it, and then adding glycerol phosphate and reacting to obtain it. The coating of the present invention has good adhesion and can be attached to metal; at the same time, it has high corrosion resistance and a long neutral salt spray resistance time; at the same time, it has good wear resistance. And the coating of the present invention also has strong aging resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of anti-corrosion coatings, and in particular relates to a phosphate-based anti-corrosion coating. Background Art

[0002] In the production of the chemical industry, due to the structure of the reaction equipment, the medium and working conditions, the equipment will suffer from corrosion problems. Especially for outdoor equipment, due to the exposure to wind and sun, the corrosion rate is faster. The corrosion of equipment has great harm to production safety, efficiency and quality. Therefore, anti-corrosion measures for equipment are very important for the chemical industry.

[0003] The types of heavy-duty anticorrosion coatings in my country mainly include epoxy anticorrosion coatings, polyurethane anticorrosion coatings, chlorinated rubber anticorrosion coatings, fluororesin anticorrosion coatings, silicone resin coatings, polyurea elastomer anticorrosion coatings, acrylic and zinc-rich primers, among which epoxy anticorrosion coatings account for the largest market share. However, epoxy coatings are usually not resistant to light and have poor salt spray resistance.

[0004] At the same time, as people's environmental awareness increases, water-based anti-corrosion coatings with green and low-toxic characteristics are gradually replacing traditional solvent-based anti-corrosion coatings and becoming a research hotspot in the coatings industry. However, the current water-based anti-corrosion coatings have poor wear resistance and corrosion resistance, and weak aging resistance. Summary of the invention

[0005] To solve at least one of the above problems, the present invention provides a phosphate-based anti-corrosion coating.

[0006] The technical solution of the present invention is a phosphate-based anticorrosive coating, which comprises, by weight: 10 to 25 parts of dihydrogen phosphate, 1 to 5 parts of polyphosphate, 1 to 4 parts of filler, 8 to 20 parts of inorganic curing agent, 1 to 5 parts of retarder, 1 to 5 parts of modified basalt fiber, and 8 to 15 parts of water;

[0007] The preparation method of the modified basalt fiber comprises the following steps: taking basalt fiber, adding acid to acid-etch it, and after the acid-etching is completed, separating, washing and drying it to obtain the acid-etched basalt fiber; taking the acid-etched basalt fiber, adding it into water and uniformly dispersing it, then adding glycerol phosphate and reacting it at 10-60° C. for 2-8 hours, taking the reaction product, and separating and purifying it to obtain the modified basalt fiber; the amount of glycerol phosphate added is 40-100% of the mass of the acid-etched basalt fiber.

[0008] In the present invention, dihydrogen phosphate, inorganic curing agent and water are the basic components of the anticorrosive coating, wherein dihydrogen phosphate is mainly used for film formation; the inorganic curing agent is used to promote the curing of dihydrogen phosphate, which is a common substance in the art, such as aluminum oxide, magnesium oxide, and some materials containing magnesium and aluminum, such as kaolin, metakaolin, magnesite, etc.; water provides the conditions and environment for curing. However, for dihydrogen phosphate, its curing speed is too fast, so it is necessary to add a corresponding retarder. As for fillers, they are common ingredients in the field of coatings and are mainly used to improve the properties of coatings, such as wear resistance, corrosion resistance, etc. As for basalt fiber, it can increase the wear resistance, crack resistance and aging resistance of the coating. However, the compatibility of conventional basalt fiber and phosphate coating is poor. Even after grafting with silane coupling agent, its performance is still relatively poor, resulting in the fact that basalt fiber is rarely added to phosphate coating in the prior art. Considering the excellent performance of basalt fiber, the inventor modified it in a new way after a large number of experiments. The final modified basalt fiber has good compatibility with phosphate coating, and the final coating has stronger performance.

[0009] When modifying basalt fiber, due to the surface characteristics of basalt fiber, we first need to acid-etch it to increase the specific surface area of ​​basalt fiber and increase the reactivity of the surface of basalt fiber; then, glycerol phosphate is used to further modify the basalt fiber. Since glycerol phosphate contains multiple hydroxyl groups and phosphate groups, it can form hydrogen bonds with phosphates, thereby increasing the compatibility of modified basalt fiber and coating. Generally speaking, the length of the basalt fiber used does not exceed 1mm, preferably not more than 0.5mm. At present, some manufacturers on the market sell basalt fiber of this size range, and it can also be made by purchasing conventional basalt fiber and crushing it.

[0010] Similar to conventional coatings, in the present invention, unless otherwise specified, all solid materials need to be crushed into powder materials, and the smaller the particle size, the better; of course, for the modified basalt fiber, it should have a certain length to meet actual needs.

[0011] Preferably, the coating comprises 15 to 18 parts of dihydrogen phosphate, 2 to 4 parts of polyphosphate, 2 to 3 parts of filler, 9 to 12 parts of inorganic curing agent, 2 to 4 parts of modified basalt fiber, and 12 to 13 parts of water.

[0012] In one embodiment of the present invention, the dihydrogen phosphate is at least one of sodium dihydrogen phosphate, potassium dihydrogen phosphate and ammonium dihydrogen phosphate. These dihydrogen phosphates are common salts in the art.

[0013] One embodiment of the present invention is that the polyphosphate is one of iron tripolyphosphate and aluminum tripolyphosphate, which are common polyphosphates in the art and can enhance the corrosion resistance of the coating.

[0014] In one embodiment of the present invention, the filler is one of nano silicon dioxide and silica fume. Nano-scale fillers can effectively increase the strength and wear resistance of the coating.

[0015] One embodiment of the present invention is that the inorganic curing agent is at least one of aluminum oxide and magnesium oxide, which are common curing agents for phosphates. These curing agents react with phosphates to solidify the phosphates.

[0016] An embodiment of the present invention is that the retarder is borax.

[0017] One embodiment of the present invention is that in the preparation process of the modified basalt fiber, the acid is one of hydrochloric acid and sulfuric acid, and the concentration of the acid is 0.5-2 mol / L, the etching time is 0.5-2h, and the etching temperature is 10-90° C. Acid etching is a common operation for modifying inorganic materials. For example, hydrofluoric acid is commonly used in the prior art to etch glass. In the present invention, in addition to hydrochloric acid and sulfuric acid, other acids can also be selected, such as common acetic acid.

[0018] One implementation of the present invention is that during the preparation process of the modified basalt fiber, continuous ultrasound is performed after adding glycerol phosphate.

[0019] In one embodiment of the present invention, the coating further comprises 5 to 12 parts of pyrophosphate and 0.1 to 0.5 parts of copper oxide. Preferably, the amount of pyrophosphate added is 7 to 9 parts, and the amount of copper oxide added is 0.3 to 0.4 parts.

[0020] Preferably, the pyrophosphate is at least one of potassium pyrophosphate and sodium pyrophosphate.

[0021] The present invention is beneficial in that:

[0022] The coating of the present invention has good adhesion and can be attached to metal; at the same time, it has high corrosion resistance and a long neutral salt spray resistance time; at the same time, it has good wear resistance and strong aging resistance. DETAILED DESCRIPTION

[0023] The present invention is further described below in conjunction with embodiments. It should be understood that the preferred embodiments described herein are only used to illustrate and explain the present invention, and are not used to limit the present invention.

[0024] In the following examples, unless otherwise specified, all operations used are routine operations in the art.

[0025] In the following examples, unless otherwise specified, all materials used are conventional materials in the art and mature commercial products.

[0026] In the following embodiments, the modifier is prepared by the following method: diethylenetriamine and dodecyl glycidyl ether in a molar ratio of 1:1 are taken, dimethyl sulfoxide is added respectively and dissolved, then the dodecyl glycidyl ether solution is added dropwise to the diethylenetriamine solution at 70°C, and the reaction is continued for 5 hours after the addition is completed. After the reaction is completed, 10 times the amount of water of the reaction solution is added, and after the layers are separated, the organic layer is taken and dried.

[0027] In the following examples, unless otherwise specified, the parts are by mass.

[0028] Example 1: In this example, the composition of the phosphate-based anti-corrosion coating is as follows: 17 parts of sodium dihydrogen phosphate, 3 parts of polyferric phosphate, 2.5 parts of nano-silicon dioxide, 11 parts of magnesium oxide, 3 parts of modified basalt fiber, 8 parts of sodium pyrophosphate, 0.35 parts of copper oxide, and 13 parts of water.

[0029] Among them, the preparation method of modified basalt fiber is as follows: prepare a hydrochloric acid solution with a concentration of 1 mol / L, take 10 parts of basalt fiber (passed through a 30-mesh sieve) and add them to 30 parts of hydrochloric acid solution, heat to 40°C and keep warm for 60 minutes, then filter out the solid phase, wash it with water several times, and dry it to obtain acid-etched basalt fiber; take 5 parts of acid-etched basalt fiber, add it to 40 parts of water and disperse it by ultrasound, add 3.5 parts of glycerol phosphate to the dispersion under continuous ultrasound and 40°C, and react for 4 hours. After the reaction is completed, take out the solid phase, wash it with water several times and dry it to obtain modified basalt fiber.

[0030] Example 2: This example is different from Example 1 in that sodium pyrophosphate and copper oxide are not added, and the amount of water added is 12 parts, and the rest are the same.

[0031] Example 3: In this example, the composition of the phosphate-based anti-corrosion coating is as follows: 17 parts of sodium dihydrogen phosphate, 1.5 parts of aluminum polyphosphate, 3.5 parts of nano-silicon dioxide, 16 parts of magnesium oxide, 4 parts of modified basalt fiber, 6 parts of sodium pyrophosphate, 0.2 parts of copper oxide, and 14 parts of water.

[0032] Among them, the preparation method of modified basalt fiber is as follows: prepare a hydrochloric acid solution with a concentration of 1 mol / L, take 10 parts of basalt fiber (passed through a 30-mesh sieve) and add them to 30 parts of hydrochloric acid solution, heat to 40°C and keep warm for 60 minutes, then filter out the solid phase, wash it with water several times, and dry it to obtain acid-etched basalt fiber; take 5 parts of acid-etched basalt fiber, add it to 40 parts of water and disperse it by ultrasound, add 3.5 parts of glycerol phosphate to the dispersion under continuous ultrasound and 40°C, and react for 4 hours. After the reaction is completed, take out the solid phase, wash it with water several times and dry it to obtain modified basalt fiber.

[0033] Example 4: In this example, the composition of the phosphate-based anti-corrosion coating is as follows: 22 parts of sodium dihydrogen phosphate, 4.5 parts of aluminum polyphosphate, 3.5 parts of nano-silicon dioxide, 10 parts of magnesium oxide, 4 parts of aluminum oxide, 2 parts of modified basalt fiber, 6 parts of sodium pyrophosphate, 0.2 parts of copper oxide, and 10 parts of water.

[0034] Among them, the preparation method of modified basalt fiber is as follows: prepare a sulfuric acid solution with a concentration of 1 mol / L, take 10 parts of basalt fiber (passed through a 30-mesh sieve) and add them to 30 parts of sulfuric acid solution, heat to 60°C and keep warm for 40 minutes, then filter out the solid phase, wash it with water several times, and dry it to obtain acid-etched basalt fiber; take 5 parts of acid-etched basalt fiber, add it to 40 parts of water and disperse it by ultrasound, add 4.5 parts of glycerol phosphate to the dispersion under continuous ultrasound and 40°C, and react for 5 hours. After the reaction is completed, take out the solid phase, wash it with water several times and dry it to obtain modified basalt fiber.

[0035] Example 5: In this example, the composition of the phosphate-based anti-corrosion coating is as follows: 23 parts of sodium dihydrogen phosphate, 3 parts of polyferric phosphate, 3 parts of silica fume, 11 parts of magnesium oxide, 3 parts of modified basalt fiber, 8 parts of sodium pyrophosphate, 0.35 parts of copper oxide, and 14 parts of water.

[0036] Among them, the preparation method of modified basalt fiber is as follows: prepare an acetic acid solution with a concentration of 1 mol / L, take 10 parts of basalt fiber (passed through a 30-mesh sieve) and add them to 30 parts of acetic acid solution, heat to 80°C and keep warm for 100 minutes, then filter out the solid phase, wash it with water several times, and dry it to obtain acid-etched basalt fiber; take 5 parts of acid-etched basalt fiber, add it to 40 parts of water and disperse it by ultrasound, add 3.5 parts of glycerol phosphate to the dispersion under continuous ultrasound and 40°C, and react for 4 hours. After the reaction is completed, take out the solid phase, wash it with water several times and dry it to obtain modified basalt fiber.

[0037] Comparative Example 1

[0038] The difference between this comparative example and Example 1 is that the modified basalt fiber is replaced by unmodified basalt fiber, and the rest are the same.

[0039] Comparative Example 2

[0040] The difference between this comparative example and Example 1 is that, in the preparation process of the modified basalt fiber, the basalt fiber is not acid-etched, and the rest are the same.

[0041] Comparative Example 3

[0042] The difference between this comparative example and Example 1 is that a silane coupling agent is used to prepare modified basalt fiber, and the preparation method of the modified basalt fiber is as follows: a hydrochloric acid solution with a concentration of 1 mol / L is prepared, 10 parts of basalt fiber (passed through a 30-mesh sieve) are added to 30 parts of the hydrochloric acid solution, the temperature is raised to 40°C and kept warm for 60 minutes, and then the solid phase is filtered out, washed with water for several times, and then dried to obtain the acid-etched basalt fiber; 5 parts of the acid-etched basalt fiber are taken, dispersed in 40 parts of a mixed solution of ethanol / water (the mass ratio of ethanol to water is 1:1), 3.5 parts of silane coupling agent KH570 are added to the dispersion under continuous ultrasound and 40°C, and the reaction is carried out for 4 hours. After the reaction is completed, the solid phase is taken out, washed with water for several times, and then dried to obtain the modified basalt fiber.

[0043] In order to further highlight the technical effects of the present invention, performance tests are performed on the above embodiments below.

[0044] Before conducting the performance test, the coating needs to be applied: take the coatings of Examples 1 to 5 and Comparative Examples 1 to 3, stir them quickly to mix them evenly to form a slurry, then clean and dry the substrate, and apply the slurry on the surface of the substrate, and cure it at room temperature for 3 days to obtain the test sample; wherein the substrate is Q235 steel.

[0045] The test was carried out according to the methods specified in GB / T 1771-2007 Determination of neutral salt spray resistance of paints and varnishes, GB / T 9286-2021 Cross-cut test of paints and varnishes, and GB / T 1768-2006 Determination of abrasion resistance of paints and varnishes by rotating rubber grinding wheel method. In the neutral salt spray resistance test, the sodium chloride concentration was 5wt% and the pH was 6.8; in the abrasion resistance test, the weight was 500g, the number of revolutions was 500 revolutions, and the speed was 60r / min. The final results are shown in Table 1.

[0046] Table 1 Performance test results of coatings of Examples 1 to 5 and Comparative Examples 1 to 3

[0047]

[0048] It can be seen from Table 1 that the coating prepared in this embodiment has strong adhesion, strong corrosion resistance and good anti-wear performance.

[0049] 2. Aging resistance test

[0050] The test samples prepared from the coatings of Examples 1 to 5 and Comparative Examples 1 to 3 were aged for 500 h using a UVA-340 ultraviolet lamp according to the method in GB / T 23987-2009 Paints and varnishes - Artificial weathering exposure of coatings - Exposure to fluorescent ultraviolet light and water. Then, the corrosion resistance, adhesion and wear resistance were tested according to the methods in GB / T 1771-2007 Determination of neutral salt spray resistance of paints and varnishes, GB / T9286-2021 Paints and varnishes cross-cut test and GB 1768:2006 Determination of wear resistance of paints and varnishes - Rotating rubber grinding wheel method. When the neutral salt spray performance test was performed, the sodium chloride concentration was 5wt% and the pH was 6.8. When the wear resistance test was performed, the weight of the weight was 500 g, the number of revolutions was 500 revolutions, and the rotation speed was 60 r / min. The final results are shown in Table 2.

[0051] Table 2 Test results of coatings after aging of Examples 1 to 5 and Comparative Examples 1 to 3

[0052]

[0053] It can be seen from Table 2 that the coating prepared in the embodiment of the present invention has strong aging resistance.

[0054] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Although the present invention has been disclosed as a preferred embodiment as above, it is not used to limit the present invention. Any technician familiar with this profession can make some changes or modify the technical contents disclosed above into equivalent embodiments without departing from the scope of the technical solution of the present invention. However, any simple modification, equivalent change and modification made to the above embodiments according to the technical essence of the present invention without departing from the content of the technical solution of the present invention still fall within the scope of the technical solution of the present invention.

Claims

1. A phosphate-based anticorrosive coating, characterized in that: Calculated by mass, it includes: 10-25 parts of dihydrogen phosphate, 1-5 parts of polyphosphate, 1-4 parts of filler, 8-20 parts of inorganic curing agent, 1-5 parts of retarder, 1-5 parts of modified basalt fiber, and 8-15 parts of water; The preparation method of the modified basalt fiber comprises the following steps: taking basalt fiber, adding acid to acid-etch it, and after the acid-etching is completed, separating, washing and drying it to obtain the acid-etched basalt fiber; taking the acid-etched basalt fiber, adding it into water and uniformly dispersing it, then adding glycerol phosphate and reacting it at 10-60° C. for 2-8 hours, taking the reaction product, and separating and purifying it to obtain the modified basalt fiber; the amount of glycerol phosphate added is 40-100% of the mass of the acid-etched basalt fiber.

2. The anticorrosive coating according to claim 1, characterized in that: The dihydrogen phosphate is at least one of sodium dihydrogen phosphate, potassium dihydrogen phosphate, and ammonium dihydrogen phosphate.

3. The anticorrosive coating according to claim 1, characterized in that: The polyphosphate is one of iron tripolyphosphate and aluminum tripolyphosphate.

4. The anticorrosive coating according to claim 1, characterized in that: The filler is one of nano silicon dioxide and silica ash.

5. The anticorrosive coating according to claim 1, characterized in that: The inorganic curing agent is at least one of aluminum oxide and magnesium oxide.

6. The anticorrosive coating according to claim 1, characterized in that: The retarder is borax.

7. The anticorrosive coating according to claim 1, characterized in that: In the preparation process of the modified basalt fiber, the acid is one of hydrochloric acid and sulfuric acid, and the concentration of the acid is 0.5-2 mol / L, the etching time is 0.5-2h, and the etching temperature is 10-90°C.

8. The anticorrosive coating according to claim 1, characterized in that: During the preparation of the modified basalt fiber, glycerol phosphate is added and then ultrasonicated continuously.

9. The anticorrosive coating according to claim 1, characterized in that: The coating also includes 5 to 12 parts of pyrophosphate and 0.1 to 0.5 parts of copper oxide.

10. The anticorrosive coating according to claim 9, characterized in that: The pyrophosphate is at least one of potassium pyrophosphate and sodium pyrophosphate.

Citation Information

Patent Citations

  • Special impregnating compound for microbial carrier basalt fiber and preparation method of impregnating compound

    CN106431016A

  • Polybutylene terephthalate material-reinforced basalt fiber special-purpose infiltrating agent and preparation method thereof

    CN106751560A